2018
DOI: 10.1039/c8ay00607e
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a two-photon fluorescent probe with a large turn-on signal for imaging hypochlorous acid in living tissues

Abstract: We have developed a new two-photon fluorescent HOCl probe (TP-HA). Fluorescence imaging shows that TP-HA is suitable for visualization of the changes of HOCl in living cells and tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
1
5
0
2
Order By: Relevance
“…A benzoylhydrazine luciferin scaffold was developed by Liang and co‐workers to realize the imaging of HClO in living MDA‐MB‐231 cells as well as in tumors in vivo. Lin and co‐workers described a two‐photon fluorescent probe TP‐HA, which has a significant “turn‐on” signal due to cleavage for the imaging of HClO in HeLa cells, RAW264.7 cells and living tissue. The probe displayed an enhanced fluorescence intensity with HClO under two‐photon excitation ( Figure ).…”
Section: Fluorescent Imaging Agents For Diagnosis Of Ros‐relevant Dismentioning
confidence: 99%
See 2 more Smart Citations
“…A benzoylhydrazine luciferin scaffold was developed by Liang and co‐workers to realize the imaging of HClO in living MDA‐MB‐231 cells as well as in tumors in vivo. Lin and co‐workers described a two‐photon fluorescent probe TP‐HA, which has a significant “turn‐on” signal due to cleavage for the imaging of HClO in HeLa cells, RAW264.7 cells and living tissue. The probe displayed an enhanced fluorescence intensity with HClO under two‐photon excitation ( Figure ).…”
Section: Fluorescent Imaging Agents For Diagnosis Of Ros‐relevant Dismentioning
confidence: 99%
“…Structure of a two‐photon HClO probe TP‐HA (above) and fluorescence images in the rat liver slice with different probe concentrations (below). Reproduced with permission . Copyright 2018, The Royal Society of Chemistry.…”
Section: Fluorescent Imaging Agents For Diagnosis Of Ros‐relevant Dismentioning
confidence: 99%
See 1 more Smart Citation
“…The Lin group reported a probe that displayed a fluorescence enhancement (≈16‐fold) in response to HOCl with high sensitivity and selectivity. The new probe was membrane‐permeable and suitable for visualization of the changes of HOCl in living cells and tissues (Scheme ) …”
Section: Introductionmentioning
confidence: 99%
“…It is endogenously generated in living organisms from hydrogen peroxide and chloride ions under the catalysis of heme-enzyme myeloperoxidase in order to kill invading bacterial pathogens. , However, excessive production of HOCL will lead to the oxidation of biomolecules, resulting in various diseases such as arthritis, atherosclerosis, and cancer. For real-time monitoring the distribution and level of endogenous HOCL, many OPEF probes for HOCL detection have been developed in the last years, but they are not suitable for tissue imaging in vivo due to short excitation wavelengths. In 2015, Chang et al first reported the TPEF probe (TP-HOCL1) for HOCL based on the oxidative deprotection of an oxathiolane group introduced onto the acedan fluorophore . Then, some TPEF probes for HOCL gradually appeared, but most of them possess the “turn-on” mechanism, which are easily interfered and unsuitable for quantitative analysis. Recently, several ratiometric fluorescence probes have been researched, which can provide two separate signals for probe and reaction product molecules avoiding the influence of environmental factors on detection. Ahn and co-workers reported a radiometric benzocoumarin probe (rTP-HOCL1) also based on the oxathiolane recognition group. Although the limit of detection is very low (34.8 nM), the emission separation (35 nm) is not large enough, which may cause spectral overlap and decrease spectral resolution .…”
Section: Introductionmentioning
confidence: 99%